Physical activity and physiotherapy: perception of women breast cancer survivors - Rangel, Jackeline (2018)
Background: Physical activity levels seem to play an important role in musculoskeletal disorders in women diagnosed with breast cancer. However, the effects of physical activity after diagnosis are not fully understood. Our purpose was to understand the importance of physical activity and physiotherapy on musculoskeletal disorders as a sequela of treatment in breast cancer survivor women. Methods: For this cross-sectional study, a sample of 94 breast cancer survivor women fulfilled a self-completed questionnaire with questions on clinical and functional variables, and levels of physical activity before and after breast cancer diagnosis. Results: All 94 women, aged between 23 and 72 years, reported at least one or more post-cancer musculoskeletal disorders. More active women reported fewer changes than the less active women (p < 0.05). For the majority of women who underwent physiotherapy after breast cancer, this intervention was perceived as helpful in the treatment of post-cancer disorders. Conclusions: Physical activity habits and physiotherapy treatments contributed to the perception of a lower number of musculoskeletal disorders. This practice should be advocated among women with breast cancer.